The house guest - Edwards, Mark. (Seattle, Washungton: Thomas & Mercer, 2020)
"When British twenty-somethings Ruth and Adam are offered the chance to spend the summer housesitting in New York, they can't say no. Young, in love and on the cusp of professional success, they feel as if luck is finally on their side. So the moment that Eden turns up on the doorstep, drenched from a summer storm, it seems only right to share a bit of that good fortune. Beautiful and charismatic, Eden claims to be a friend of the homeowners, who told her she could stay whenever she was in New York. They know you're not supposed to talk to strangers - let alone invite them into your home - but after all, Eden's only a stranger until they get to know her. As suspicions creep in that Eden may not be who she claims to be, they begin to wonder if they've made a terrible mistake ..."--Publisher description
Keywords: Detectives and mystery; Housesitting -- Fiction; Missing persons -- Fiction